What activities do textbooks designed to teach Geology propose? - Pardo Santano, Pablo (Pulso. Revista de educación, 2004)
This article examines the educational resources that employ a substantial collection of books designed to teach Geology across various key stages in compulsory education. Various categories of analysis are established, and an in-depth examination of the materials is conducted to draw conclusions regarding the educational priorities of the authors, the scientific concepts conveyed in the books they produce, or the relevance and usefulness of the textbooks and information contained.